Skin symptoms (allergic and non-allergic) predicting the development of allergic respiratory outcomes and asthma in bakers - Chongo-Faruk, Vânia (Department of Public Health and Family Medicine, 2020)
Background: Recent studies have suggested that aside from the inhalational route, skin exposure may also play an important role in the sensitization to allergens, resulting in adverse allergic respiratory outcomes including asthma in workers exposed to these agents. This appears to be reported more commonly for low molecular weight agents such as isocyanates and some cleaning agents. This study investigated whether skin symptoms, in the presence or absence of allergic sensitization, can predict the development of allergic respiratory outcomes and asthma in bakery workers. Methods: A cohort study investigated 263 bakery workers using a modified ECRHS questionnaire; immunological tests including skin prick tests for common local aeroallergens (ALK-Abello´ A/S, Horsholm, Denmark), Phadiatop and serum-specific IgE to bakery allergens (wheat, rye and fungal α-amylase); and pulmonological tests including spirometry, non-specific bronchial hyperresponsiveness, and fractional exhaled nitric oxide (FeNO), after a 4 year period. Results: Workers’ median age was 32 years (IQR: 26-38), 50% were female, 54% were ever smokers and 32% were atopic. At baseline, 26% of workers were sensitized to bakery allergens, skin symptoms were present in 22% and 11% reported work-related skin symptoms (WRSS). 3 While the incidence of general upper (19%) and lower (22%) respiratory symptoms over the follow-up period were very similar, work-related upper (29%) respiratory symptoms were higher than lower (20%) respiratory symptoms. However, the incidence of allergic sensitization to bakery allergens was only 8% and a new asthma diagnosis present in 4% over this period. In multivariate adjusted (gender, atopy and smoking status) regression models, having a history of skin symptoms was associated with an increased risk of developing work-related lower respiratory symptoms - WRLRS (RR=2.2, 95% CI: 1.03-4.83), while having clinically significant symptoms of eczema or urticaria was associated with an increased risk of reporting general upper respiratory symptoms (RR=5.5, 95% CI: 1.30-24.20) as well as WRLRS (RR= 4.8, 95% CI: 1.60-14.40). Furthermore, WRSS was associated with an increased risk of general upper respiratory symptoms (RR=5.1, 95% CI: 1.31-19.81), WRLRS (RR=4.1, 95% CI: 1.43-11.85) and elevated FeNO levels (FeNO>25ppb: RR=2.9, 95% CI: 1.19-7.28). The association between clinically significant skin symptoms or WRSS and new onset upper or lower respiratory symptoms were modified by use of dermal personal protective equipment. Infrequent or absent glove usage was associated with a higher risk (RR=5.3, 95% CI: 1.54-18.43) of having new onset WRLRS. Conclusion: Skin symptoms, more so if work-related, appear to be associated with future development of general and work-related upper and lower respiratory symptoms and inflammatory markers suggestive of asthma in bakery workers.